(untitled) (Praxis Educativa, 2025)
This paper seeks to contribute to the conceptual precision of the notion of socio-educational inequalities, emphasizing the differentiation between social and educational dimensions from a perspective anchored in multiple inequalities. On the one hand, social class of origin, gender, health conditions, ethnic-racial status, the obligation to care for others, and place of residence constitute a multiplicity of dimensions of inequalities external to the school institution, extracurricular factors that the school "receives" as givens. Meanwhile, there are another series of factors that shape educational inequalities, produced within the school context: the construction of different modes of relating to knowledge, the classification of students into groups according to different criteria, the work and qualifications of teachers, the infrastructure (condition of buildings, cleanliness, laboratory facilities, access ramps), as well as the relationship fostered with higher education, all of which contribute to strictly academic work. In this sense, this last dimension is no longer (or no longer only) about the reproduction of extracurricular inequalities, but rather about the production of educational inequalities: the fruits of school action (or lack of action).